Developing learner autonomy in Vietnamese students studying on an Academic English program. - Harrold, Peter (2015)
Learner Autonomy is an attribute of particular importance for students to develop when transitioning to tertiary level due to the demands placed on them to take greater responsibility for their learning. This study explores the attitudes and approaches of teachers and students to developing Learner Autonomy in the specific context of a language centre in Vietnam, that focuses on Academic English in order for students to study overseas. It was motivated by concerns often expressed in the literature (Dang, 2010; Humphreys & Wyatt 2014; Le, 2013; Nguyen, 2009) that due to their cultural and education heritage students in the context of Vietnam often need greater support to develop their capacity to learn autonomously. The study took an action research approach, and collected data via a survey of the students priorities and approaches to developing autonomy, as well as focus group discussions with teachers on the role learner autonomy plays in teaching and learning at the language centre. This information was then used to develop an approach for promoting autonomy via resource-based teacher workshops that targeted the needs identified by the students and teachers as well as the cultural considerations highlighted in the literature. The findings of the research illustrate how a practical resource-based approach, that offers greater choice to both teachers and learners is a sustainable method for assisting students in developing as autonomous learners. Therefore, it is a recommendation of this study to maintain and build the resource base digitally on a wiki, and add to it specifically in the area of technology enhanced language learning.